EKSPLORASI PEMANFAATAN ASET DAERAH OLEH UMKM SEBAGAI SUMBER POTENSI PENDAPATAN ASLI DAERAH - Susiastini, Anissa; Fikri, Ali (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting Regional Original Revenue (PAD). In Mataram City, many MSMEs use public assets, but their contribution to PAD is still limited. This study aims to analyse the utilisation of regional assets by non-tax MSMEs and formulate strategies to optimise their contribution to PAD.Methods: This study uses a qualitative phenomenological approach to explore how non-tax MSMEs in Mataram City utilise regional assets. Data were obtained through interviews, observations, and documentation, then analysed using a case study method.Results: The findings reveal that the utilisation of regional assets by non-tax MSMEs in Mataram City has contributed positively, though not optimally, to Regional Original Revenue (PAD). Most MSMEs with daily revenue above Rp1,000,000 have not yet fulfilled their tax obligations, instead paying through rental and sanitation fees. The study also indicates that regulatory clarity, asset inventory, and improved public facilities are key strategies for optimising MSMEs’ productivity and increasing PAD contribution.Conclusion and Suggestion: Although the contribution of Micro, Small, and Medium Enterprises (MSMEs) to Regional Original Revenue (PAD) in Mataram City remains limited, they play an essential role in utilising regional assets and supporting local economic growth. Only a small portion of MSMEs contribute through taxes or levies, while most help the economy indirectly through employment and innovation. The study suggests that local governments should improve asset management, adjust contribution schemes, and provide better facilities to enhance MSME productivity and long-term contributions to PAD. Keywords: Micro, Small, and Medium Enterprises (MSMEs); Regional Assets; Regional Original Revenue (PAD); Local Economic Growth; Mataram City